Analisis Yuridis Perceraian Disebabkan Suami Biseksual (Studi Putusan Pengadilan Agama Pariaman Nomor 69/Pdt.G/2019/Pa.Prm) - Raina Liza Liza (Universitas Harapan Medan, 2022)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming an eternal and happy family based on God Almighty. (Law No. 1 of 1974). Divorce is the breaking of marital ties between husband and wife by court decision and there are sufficient reasons that between husband and wife will not be able to live in harmony again as husband and wife. Bisexual is a person who has sexual attraction to two different genders at once. What are the legal consequences that are born after the breakup of a marriage because the husband is bisexual, How are the judges' considerations in deciding divorce cases because the husband is bisexual. The type of research used is normative juridical obtained from library materials. The nature of this research is descriptive analysis, namely to obtain a systematic, factual and accurate description of the problems studied. Collecting data in this study through library research with data collection tools using library research and interviews. Bisexual behavior can be used as a reason to sue for divorce because the purpose of marriage law is to create peace in the household and society and avoid the benefit that destroys the human generation. The legal consequences that were born after the termination of the marriage because the husband was bisexual were experiencing conflict, inharmonious communication relationships, the existence of mafsadat and maslahat elements as well as making the marriage divorced. The judge's consideration in deciding divorce cases because the husband is bisexual is that there is harm in one of the partners, there are 6 (six) ).